Find arsinh(x) in terms of x

let y=arsinh(x)x=sinh(y)=(ey - e-y)/22x=e- e-y2x*ey=ey-1 (multiply byey)0=(ey)2-2xey-1This is a quadratic in ey with coefficients: a=1,b=-2x,c=-1Usinng the quadratic formula (and simplifying):e^y=x +/- sqrt(x2+1)but ey=x-sqrt(x2+1) isn't possible as ey>0 for all y.so ey=x+sqrt(x2+1)y=ln(x+sqrt(x2+1))arsinh(x)=ln(x+sqrt(x2+1)).(Note that sqrt(x) is standard notation for 'the square root of x' on computers).

Related Further Mathematics A Level answers

All answers ▸

Using the definitions of hyperbolic functions in terms of exponentials show that sech^2(x) = 1-tanh^2(x)


Find the Taylor Series expansion of tan(x) about π/4 up to the term in terms of (x-π/4)^3.


Where does Euler's Formula come from?


How to multiply and divide by complex numbers


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences